Trial of labor after previous cesarean delivery (TOLAC) and association of BMI and previous vaginal delivery with frequency of VBAC (Bangladesh Journal of Medical Science, 2016)
Objectives: To determine the frequency of successful Vaginal Birth after One Cesarean Section in our tertiary care institution and to determine the causes of its failure.Material and Methods: This study was conducted in department of Obstetrics and Gynecology of Shifa International Hospital and Shifa Foundation Community Health Centre Islamabad Pakistan from Feb 2011 to Dec 2014. This study included 592 patients who presented in labor room emergency reception of Obs/Gynae department at term with previous one scar having fulfilled the laid down inclusion criteria for VBAC during ante-natal care. The patients were admitted in hospital and were allowed to proceed for spontaneous labor under vigilant monitoring on complications of trial of scar. Immediate emergency cesarean sections were performed, where indicated.Results: Out of 592 patients 70.7% were delivered vaginally after previous one cesarean section and 29.3% had emergency cesarean section. Leading indications for repeat cesarean section was fetal distress, failure to progress and scar tenderness. No maternal and fetal complication occurred in our study. The success rate of Trial of labor after one previous cesarean delivery was lower in obese (64.38%) as compared to non-obese women (82.06%) (p